Colletotrichum gloeosporioides Cg2LysM contributed to virulence toward rubber tree through affecting invasive structure and inhibiting chitin-triggered plant immunity - Zhao, Li; Liao, Zhiwen; Feng, Liping; An, Bang; He, Chaozu; Wang, Qiannan; Luo, Hongli (Frontiers in Microbiology, 2023)
Fungal chitin, as a typical microorganism-associated molecular pattern (PAMP), was recognized by plant LysM-containing protein to induce immunity called pattern-triggered immunity (PTI). To successfully infect host plant, fungal pathogens secreted LysM-containing effectors to inhibit chitin-induced plant immunity. Filamentous fungus Colletotrichum gloeosporioides caused rubber tree anthracnose which resulted in serious loss of natural rubber production worldwide. However, little is known about the pathogenesis mediated by LysM effector of C. gloeosporioide. In this study, we identified a two LysM-containing effector in C. gloeosporioide and named as Cg2LysM. Cg2LysM was involved not only in conidiation, appressorium formation, invasion growth and the virulence to rubber tree, but also in melanin synthesis of C. gloeosporioides. Moreover, Cg2LysM showed chitin-binding activity and suppression of chitin-triggered immunity of rubber tree such as ROS production and the expression of defense relative genes HbPR1 and HbPR5. This work suggested that Cg2LysM effector facilitate infection of C. gloeosporioides to rubber tree through affecting invasive structure and inhibiting chitin-triggered plant immunity.